Development of Problem Based Differentiated Learning Comparison Materials in Junior High School - Meriza, Dyna; Hiltrimartin, Cecil; Hartono, Yusuf (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2024)
The importance of differentiated learning in the classroom is to meet students' diverse learning needs, increase engagement, and maximize individual potential so that each student can achieve optimal learning outcomes. This research was carried out as a starting point in the use of differentiated learning modules on problem-based comparison materials so that students' mathematical problem-solving skills are good, but there are still many learnings that do not integrate student needs, and students still experience difficulties in understanding comparative materials. The type of research used is development studies-type design research with the aim of producing a problem-based differentiated learning module on comparative materials that is valid, practical, and has a potential effect of using differentiated learning modules of comparative materials on students' mathematical problem-solving skills. The research subjects were 36 students of class VII.8 of junior high school 17 Palembang. The data collection techniques used were questionnaires, tests, and interviews. The results showed that the problem-based differentiated learning module on comparison material was quite valid with an average percentage of 82.9% and very practical with an average percentage of 83.3%, and students had good mathematical problem-solving skills with an average percentage of 83.069% after the implementation of learning. The resulting teaching module contains lesson plans, student worksheets, teaching materials, assessments, and assessment rubrics.